Stretchable Textile Yarn Based on UHF RFID Helical Tag - Sofia Benouakta; Florin Doru Hutu; Yvan Duroc (Textiles, 2021)
In the context of wearable technology, several techniques have been used for the fabrication of radio frequency identification (RFID) tags such as 3D printing, inkjet printing, and even embroidery. In contrast to these methods where the tag is attached to the object by using sewing or simple sticking, the E-Thread® technology is a novel assembling method allowing for the integration of the RFID tag into a textile yarn and thus makes it embeddable into the object at the fabrication stage. The current E-Thread® yarn uses a RFID tag in which the antenna is a straight half-wave dipole that makes the solution vulnerable to mechanical strains (i.e., elongation). In this paper, we propose an alternative to the current RFID yarn solution with the use of an antenna having a helical geometry that answers to the mechanical issues and keeps quite similar electrical and radiative properties with respect to the present solution. The RFID helical tag was designed and simulated taking into consideration the constraints of the manufacturing process. The helical RFID tag was then fabricated using the E-Thread® technology and experimental characterization showed that the obtained structure exhibited good performance with <semantics>10.6 m</semantics> of read range in the ultra high frequency (UHF) RFID band and <semantics>10%</semantics> of tolerance in terms of elongation.